Michel Gerard : Observatoire Geomnesique. - Temkina, Marina (Montigny les Metz : Editions Voix Richard Meier, 1990)
This book presents fourteen drawings and one poem that arose from an encounter between the pet and the artist.
Frans
Russisch
boek
Keywords: Gerard, Michel